If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (t + 3)(t + 8) = t(t + 5) + 168 Reorder the terms: (3 + t)(t + 8) = t(t + 5) + 168 Reorder the terms: (3 + t)(8 + t) = t(t + 5) + 168 Multiply (3 + t) * (8 + t) (3(8 + t) + t(8 + t)) = t(t + 5) + 168 ((8 * 3 + t * 3) + t(8 + t)) = t(t + 5) + 168 ((24 + 3t) + t(8 + t)) = t(t + 5) + 168 (24 + 3t + (8 * t + t * t)) = t(t + 5) + 168 (24 + 3t + (8t + t2)) = t(t + 5) + 168 Combine like terms: 3t + 8t = 11t (24 + 11t + t2) = t(t + 5) + 168 Reorder the terms: 24 + 11t + t2 = t(5 + t) + 168 24 + 11t + t2 = (5 * t + t * t) + 168 24 + 11t + t2 = (5t + t2) + 168 Reorder the terms: 24 + 11t + t2 = 168 + 5t + t2 Add '-1t2' to each side of the equation. 24 + 11t + t2 + -1t2 = 168 + 5t + t2 + -1t2 Combine like terms: t2 + -1t2 = 0 24 + 11t + 0 = 168 + 5t + t2 + -1t2 24 + 11t = 168 + 5t + t2 + -1t2 Combine like terms: t2 + -1t2 = 0 24 + 11t = 168 + 5t + 0 24 + 11t = 168 + 5t Solving 24 + 11t = 168 + 5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5t' to each side of the equation. 24 + 11t + -5t = 168 + 5t + -5t Combine like terms: 11t + -5t = 6t 24 + 6t = 168 + 5t + -5t Combine like terms: 5t + -5t = 0 24 + 6t = 168 + 0 24 + 6t = 168 Add '-24' to each side of the equation. 24 + -24 + 6t = 168 + -24 Combine like terms: 24 + -24 = 0 0 + 6t = 168 + -24 6t = 168 + -24 Combine like terms: 168 + -24 = 144 6t = 144 Divide each side by '6'. t = 24 Simplifying t = 24
| 18-2z=6-4 | | -6y=36x-72 | | 2x^3+4x^2+10x=0 | | 7x-2=34+x | | 4y+7y=66 | | 5n+10-8=2x | | 13a+50=360 | | 2(x-7)+3(x-1)=4+3 | | 4x+4y=-32 | | X+18=-4 | | 2y^2-7=25 | | x-4/8=15 | | -3(8x+2)+4(5x-1)= | | (3x^2y-xy)dx+(2x^3y^2+x^3y^4)dy=0 | | 3/5x-4=2 | | x-14=66 | | -5x-6=x-48 | | 4(-5x+8)-(x+5)=-15 | | 9xm+19=55 | | 4(-3x-6)= | | m(m-7)= | | 2*x-7=1 | | -2w-3(4z-5w)-32= | | 4c-3d=-20 | | 2x^2+4x-31=0 | | 3+ln(27x)=18-2ln(x) | | 2(y+3y)=84 | | 7(7x+6y-9)+4(8x-4)= | | -9x-10+3x-4= | | 3*x+4=1 | | 21=60-12x | | a+(10-3)=30+10a |